Economic Growth and the Volatility of Foreign Aid - Michal Chervin; Sweder van Wijnbergen (Tinbergen Institute, 2010)
Foreign aid's effectiveness in promoting economic growth remains mired in controversy.We examine the impact of the volatility of aid on economic growth, controlling for the level of aid. A four-year panel analysis is conducted encompassing 155 countries over the period 1966-2001. We find that once the volatility of aid is controlled for, aid has a positive impact on economic growth. Correspondingly, volatility of aid flows is found to be negatively related to growth. We found no significant link between investment and foreign aid, but a positive correlation between aid and consumption and a negative link between aid volatility and consumption. But our results also indicate that aid has become a source of volatility rather than insuring against it, and in that way may have become inimical to economic growth.
Keywords: O4; O11; O19; 330; foreign aid; volatility; economic growth; Entwicklungshilfe; Volatilität; Wirtschaftswachstum; Schätzung; Welt